Secondary Metabolites Produced by Coculture of Pleurotus ostreatus SY10 and Pleurotus eryngii SY302. Issue 4 (28th February 2022) - Ge, Xiaoxuan; Wang, Yu; Sun, Chunxiao; Zhang, Ziping; Song, Lin; Tan, Lingling; Li, Dehai; Yang, Song; Yu, Guihong
Abstract: A new isovaleryl‐monoterpene, pleurotusin A (1 ), and a new cyclopentenone derivative, pleurotusin B (7 ), together with five related known terpenoids (2 –6 ), were isolated from the coculture broth of two edible fungi, Pleurotus ostreatus SY10 and Pleurotus eryngii SY302. The absolute configurations of 1 and 7 were elucidated by comprehensively using the density functional theory calculation of NMR and ECD data, DP4+ probability analysis, Mo2 (OAc)4 ‐based CD experiment and optical rotation. The antimicrobial activities of these compounds except for the unstable compound 7, were evaluated against two types of human‐pathogenic fungi, Candida albicans and Cryptococcus neoformans, and three types of human‐pathogenic bacteria, Staphylococcus aureus, Escherichia coli, and Shigella sp. Compound 1 displayed moderate activity against S. aureus with an MIC50 value of 90.3 μM. In addition, the antioxidant activities of high‐yielding 2 –6 were tested using DPPH, and compound 4 showed moderate activity with an EC50 value of 573 μM. Abstract :